Management of Diplopia from Multiple Cranial Nerve Palsies: A Case Report. - Tran, Nguyen (Optometry & Visual Performance, 2019)
Background: In a patient with an acquired noncomitant deviation, recent-onset diplopia is a very distressing problem. Initial management includes correction of significant refractive error, occlusion to prevent diplopia, prescription of Fresnel prism to allow for binocular fusion and vision therapy. This case report will show the benefit of treatment. Case Report: A patient was referred by his optometrist for the evaluation and treatment of recent-onset diplopia. Exam findings were remarkable for right cranial nerve IV and right cranial nerve VI palsies that presented as binocular diplopia. The patient was followed over the course of 3 months, during which occlusion and Fresnel prism were used in the management and treatment of his diplopia. Conclusion: This case illustrates how optometric management methods facilitated the recovery of a patient with cranial nerve IV and VI palsy.